2008
DOI: 10.1007/s10457-008-9110-0
|View full text |Cite
|
Sign up to set email alerts
|

Underutilized agroforestry food products in Amazonas (Venezuela): a market chain analysis

Abstract: The worlds' current food production system is focused on a limited number of crops. However, international food demand is increasingly looking for more diversified supplies. In the Venezuelan State Amazonas, the Piaroa indigenous people collect and cultivate several indigenous species with local, regional, national and even international potential. A participatory approach was used to select, in cooperation with these Piaroa people, a list of products for in-depth economic analysis and for introduction in agro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The commercialization of these secondary products is apparently hampered by a lack of ready markets and low production volumes. In order to promote this trade, however, it would be necessary to increase the numbers of trees of the harvested species (Looy et al 2008). This practice may lead to reductions in tree species diversity and increases in the densities and frequencies of exotic tree species growing in cabrucas, which would not be positive for conservation purposes.…”
Section: Strategies For Increasing Profitability and Conservation Impmentioning
confidence: 99%
“…The commercialization of these secondary products is apparently hampered by a lack of ready markets and low production volumes. In order to promote this trade, however, it would be necessary to increase the numbers of trees of the harvested species (Looy et al 2008). This practice may lead to reductions in tree species diversity and increases in the densities and frequencies of exotic tree species growing in cabrucas, which would not be positive for conservation purposes.…”
Section: Strategies For Increasing Profitability and Conservation Impmentioning
confidence: 99%
“…We identified 10 high-potential NUS for which agroforestry specialists in the Peruvian Amazon indicated that they have a high commercial, ecological and nutritional value. The species status of NUS is confirmed in other studies, which mention them as underutilized [43], "cinderella species" [44,45], undervalued [46] or more recently included them in a list of pantropical NUS fruit [14].…”
Section: Identification Of High-potential Nusmentioning
confidence: 60%
“…The few chaya vendors that were encountered in the markets faced high transaction costs that prevented them from visiting markets frequently and selecting more profitable ones, a situation due to the fact that they are living in remote areas, distant from each other, and operating individually. This situation affects numerous crops grown in remote areas, where the transaction costs of bringing the products to market can be unrealistic (Gruère et al 2008;Van Looy et al 2008). Perishability did not stand out in the interviews as a constraint for marketing chaya, but other authors have determined it to be a key factor limiting wider supply and marketability-a condition that can be overcome by dehydrating the leaves (Caceres et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A Rapid Market Appraisal (RMA) method was applied to collect qualitative information from producers, traders, consumers, and other value chain actors (Ferris 2012;Holtzman 2003), which was complemented by interviews with experts, literature review, and internet searches. Variations of this approach have been applied to assess the value chains of other neglected and underutilized species in other regions (Bandula et al 2016;Van Looy et al 2008). We expected that multiple problems exist at different points in the value chain for chaya related to production, commercialization, and consumer demand that limit its integration into the mainstream food system.…”
Section: Introductionmentioning
confidence: 99%